What is the next chapter in the organized food retail industry in Portugal, up to 2030, and what are the strategic options that should be considered for strategy formulation? - the future evolution of the payments industry in Portugal - Henriques, Mariana Crisóstomo (2022)
This project focus on the analysis of the organized food retail industry in Portugal, up to 2030. For this purpose, four scenarios were created using two critical uncertainties-shoppers’ e-commerce usage and producers’ direct-to-consumer adoption-and recommendations were developed. Furthermore, the future of the payments industry was analysed since payment is still a critical phase in food retailers’ customer journey. This analysis was developed using the lenses of customers, retailers, banks and new entrants. One can conclude we are moving towards a cashless and contactless society, and end-to-end services, customization and security will be the main focus of the industry.